SPEECH ACTS FOR SUPPORTING ENGLISH TEACHING AND LEARNING - Yelfiza Yelfiza (International Conference on Languages and Arts, 2013)
This research studied about speech acts used by the English lecturers at STKIP, who taught at the fifth semester at 2012 academic year. The researcher wanted to answer the questions about kinds of speech acts used by the lecturers, and which speech acts that supported language teaching. The method of the research was ethnomethodology. Instruments of the research were video and notebook. The number of participants was six lecturers. Sampling techniques was purposive sampling and data were analyzed by descriptive analysis. Based on the data analysis, finding can be sated as follows. Speech acts used by the lecturers can be categorized into eight types. They are asserting, announcing, informing, questioning, commenting, clarifying, praising, and commanding. Kinds of speech acts were influenced by the lecturers’ culture. The more interactive lecturers produced more speech acts. Otherwise, the less interactive lecturers produced less speech acts. Finally, speech acts are categorized based on its benefits to the teaching improvement. Some speech acts are judged not effective but some others were not effectiveKey words: Speech acts, English, lecturers, teaching, learning